AB1081 Efficacy and safety of canakinumab vs triamcinolone acetonide in persistent or elderly gouty arthritis patients. (23rd January 2014) - Alten, R.; Bloch, M.; Bardin, T.; So, A.; Shpilsky, A.; Nebesky, J.M.; Kiechle, T.; Schlesinger, N.
Abstract : Background: Gouty arthritis (GA), in the elderly, often remains misdiagnosed or diagnosed late in its clinical course and differs from classical GA as more indolent and recurrent. GA patients (pts) with either long-standing disease (>10 yrs) or advanced age (≥65 yrs) are at higher risk for co-morbidities which may limit treatment options vs the general population. Canakinumab, a fully human anti-IL-1β monoclonal antibody, potentially offers a new therapeutic option. Objectives: Evaluate the efficacy and safety of canakinumab vs triamcinolone acetonide (TA) in persistent or elderly GA pts. Methods: In two 12-week multi-center, double-blind, double-dummy, active-controlled studies (β-RELIEVED, N=228; β-RELIEVED II, N=226), pts ≥18-≤85 yrs meeting ACR 1977 preliminary criteria for GA and contraindicated, intolerant or refractory to NSAIDs and/or colchicine, with onset of flares ≤5 days were randomized to receive single dose canakinumab 150mg sc or TA 40mg im, and were re-dosed "on demand" on each new flare. Upon completion of core studies, pts enrolled into 12-week extension studies and received canakinumab 150 mg sc or TA 40 mg im "on demand" for new flare. Post-hoc analysis was carried out on GA pts (age ≥65 yrs or GA for >10 yrs) to analyze the efficacy and safety of canakinumab vs TA. Results: Of 212 pts (94 in canakinumab group, 118 in TA group) included in the subgroup (β-RELIEVED, N=228; β-RELIEVED II, N=226) 81(35.7%) pts were aged ≥65 yrs and 165 (77.8%) had GA for >10 yrs (69, 73.4% in canakinumab group and 96, 81.4% in TA group). After 24 weeks treatment there was a significant (58%) risk reduction in time to first new flare with canakinumab vs TA (hazard ratio 0.42; 95% CI 0.26 to 0.68; p=0.0002 [one sided]). Mean pain intensity post-dose on VAS at 72h was lower for canakinumab vs TA (LS mean: 26.6 vs 36.3, p=0.0085). The incidence of adverse events (AEs) was 73.4% for canakinumab vs 55.1% for TA. Infections and infestations were reported in 21.3% pts with canakinumab vs 8.5% in TA. Most common infections with canakinumab were urinary tract infections (3.2%), followed by nasopharyngitis, pneumonia, sinusitis, and upper respiratory tract infections (URTI) (2.1% each) vs nasopharyngitis, pneumonia (0.8% each) and URTI (1.7%) in TA group. AEs reported in >5% pts were hypertension, arthralgia, increased gamma-glutamyl transferase and back pain (5.3% each) with canakinumab vs hypertension (6.8%) in TA. Serious AEs were reported in 8.5% and 3.4% pts treated with canakinumab and TA, respectively. Pneumonia was reported in one pt in canakinumab group and he responded to treatment. One pt (TA) had pulmonary embolism and died due to cardiac death. Conclusions: Canakinumab provided superior pain relief and reduced the risk of a new flare vs TA in this subgroup of pts with persistent GA or elderly pts with GA. Thus it may represent a treatment alternative given that these pts are at a higher risk of comorbidities and may have more limitations to currently available treatments. Disclosure of Interest: R. Alten Grant/Research support from: Novartis, Consultant for: Novartis, Speakers Bureau: Novartis, M. Bloch Grant/Research support from: Novartis, T. Bardin Grant/Research support from: Menarini, Consultant for: Novartis, Ipsen, Menarini, Ardea, Biocryst, A. So Grant/Research support from: Novartis, Consultant for: Novartis, Ardea, Speakers Bureau: Novartis, Ardea, Menarini, A. Shpilsky Shareholder of: Novartis, Employee of: Novartis, J. M. Nebesky Employee of: Novartis, T. Kiechle Shareholder of: Novartis, Employee of: Novartis, N. Schlesinger Grant/Research support from: Novartis, Consultant for: Novartis, URL Pharma, Savient, Takeda, Rx Enzyme, Speakers Bureau: Novartis, Takeda, Savient